2014
DOI: 10.1111/cea.12287
|View full text |Cite
|
Sign up to set email alerts
|

Local increase in IgE and class switch recombination to IgE in nasal polyps in chronic rhinosinusitis

Abstract: The current study suggests local class switching to IgE, production of IgE and IgE localization to the surface of mast cells in eosinophilic chronic rhinosinusitis in the Japanese population. The difference in the IgE-related profiles between eosinophilic chronic rhinosinusitis and non-eosinophilic chronic rhinosinusitis suggests heterogeneity in the pathogenesis of chronic rhinosinusitis with nasal polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 34 publications
4
35
0
Order By: Relevance
“…34 Baba et.al., demonstrated local increase in total IgE, as well as class switch recombination to IgE in nasal polyps in chronic rhinosinusitis. The Th2 inflammatory pathway, and increased concentrations of IL-5 and total IgE, are proposed to play a role in the pathogenesis of CRSwNP 35 That increased IgE levels are reported in CRSwNP, coupled with the current findings that cells with cytoplasmic IgG are also elevated in this population, suggests mature B cells may migrate and localize to polyp tissue. Factors that govern class-switch recombination and further tissue specific differentiation of plasma cells warrant further investigation.…”
Section: Discussionmentioning
confidence: 65%
“…34 Baba et.al., demonstrated local increase in total IgE, as well as class switch recombination to IgE in nasal polyps in chronic rhinosinusitis. The Th2 inflammatory pathway, and increased concentrations of IL-5 and total IgE, are proposed to play a role in the pathogenesis of CRSwNP 35 That increased IgE levels are reported in CRSwNP, coupled with the current findings that cells with cytoplasmic IgG are also elevated in this population, suggests mature B cells may migrate and localize to polyp tissue. Factors that govern class-switch recombination and further tissue specific differentiation of plasma cells warrant further investigation.…”
Section: Discussionmentioning
confidence: 65%
“…6 Several groups also found B cell clusters and B cell follicle-like structures in NPs. 121124 However, unlike the germinal center, the structure of these local follicles was not well organized (Fig. 2I).…”
Section: B-lineage Cellsmentioning
confidence: 99%
“…123 Interestingly, Cao et al and Baba et al reported that local IgE production and IgE class switch recombination were found only in eosinophilic NPs but not in non-eosinophilic NPs in China and Japan. 97,124 …”
Section: B-lineage Cellsmentioning
confidence: 99%
“…Local, rather than systemic IgE, is thought to be responsible for the inflammatory process in CRSwNP and eCRS. Total IgE and the number of IgE‐positive cells in tissue have been shown to be elevated in the nasal polyp tissue in patients with eCRS compared with non‐eCRS . Additionally, raised total IgE in nasal polyps is significantly associated with elevated interleukin 5 (IL‐5) and eosinophil cationic protein levels, implying a correlation between IgE and eosinophilic inflammation.…”
mentioning
confidence: 99%